Forschungspotenziale von Universitäten und Wirtschaft in Deutschland: „Scientific Wealth” im interregionalen Vergleich - Liefner, Ingo (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
Theoretical considerations suggest that scientific research can stimulate industrial research and development activities on a regional level (spillover). This article uses public funding of scientific institutions, research grants, industrial spending on research and development, and paents as indicators to investigate the relation between science and industry statistically. However, the analyses show that the spatial distribution of industrial R&D activities in Germany cannot be explained by the existence of regional spillovers between science and industry alone.